METHODOLOGICAL AND PROGRAM PECULIARITIES OF USAGE OF SOCIAL SERVICES IN DISTANCE LEARNING SYSTEMS (Journal of Information Technologies in Education (ITE), 2012)
In article the methodological and software peculiarities of social services usage in distance learning system “Kherson Virtual University” is considered.
Keywords: API; distance learning; distance learning system; JSon; social service; widget